2021
DOI: 10.2147/ijgm.s285757
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Deoxynucleotidyl Transferase Commonly Expresses in Germ Cell Tumors: Evaluation on a Large Series from Multiple Centers

Abstract: The concrete features of expression of terminal deoxynucleotidyl transferase (TdT) are needed to be revealed in male and female germ cell tumors (GCTs). Methods: TdT immunostaining was performed in 195 GCTs, and the tumor and/or tumorous components included seminomas, germ cell neoplasias in situ (GCNISs), dysgerminomas, embryonal carcinomas (ECs), extragonadal germinomas, yolk sac tumors (YSTs), teratomas, and spermatocytic tumors. Twenty-one sex cord-stromal tumors were also added. Expression of the classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(36 reference statements)
1
1
1
Order By: Relevance
“…A subsequent study by Gayhart et al utilizing the same clone revealed TdT expression in 4/25 seminomas (16%), 6/12 germinomas (50%), and 1/3 dysgerminomas (33%) [7]. Another study on a larger population (n = 192) reported frequency of TdT expression very similar to our cohort [8]. None of the aforementioned studies analyzed the association between the level of immunohistochemical expression of TdT and clinicopathological characteristics.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A subsequent study by Gayhart et al utilizing the same clone revealed TdT expression in 4/25 seminomas (16%), 6/12 germinomas (50%), and 1/3 dysgerminomas (33%) [7]. Another study on a larger population (n = 192) reported frequency of TdT expression very similar to our cohort [8]. None of the aforementioned studies analyzed the association between the level of immunohistochemical expression of TdT and clinicopathological characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…One study postulated that long-term storage of paraffin-embedded GCT tissues may lead to losing their TdT detectability [8]. In contrast, we observed that deeper parts of the tumor show lower (if any) reactions than superficial areas, where the formalin penetration is more efficient.…”
Section: Discussioncontrasting
confidence: 56%
“…Although AFP and β-hCG levels were not available for the patient of the current report upon admission, postoperative examination revealed elevated levels of both markers. Zhou et al ( 16 ) discovered that terminal deoxynucleotidyl transferase can serve as a novel tumor marker for diagnosing seminoma, germ cell tumor in situ , anaplastic cell tumor, embryonal carcinoma and mixed germ cell tumor with a markedly high positive rate. Furthermore, research has demonstrated that plasma levels of microRNA-371a-3p can be used as an indicator for prognostic assessment of germ cell tumors ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, markers for these tumors are still being tested and discovered. For example, one study reported that terminal deoxynucleotide transferase (TdT) can be used as a new IHC marker for the diagnosis of various extragonadal GCTs with a high positive rate in seminomas (99%, 107/108), ECs (100%, 15/15), and extragonadal germinomas (100%, 11/11) and absence in YSTs (0/38) and teratomas (0/19) ( 60 ). More clinical trials targeting various types of EGCTs are expected in the future.…”
Section: Immunological Diagnosismentioning
confidence: 99%